2023
DOI: 10.3389/fpubh.2023.1017483
|View full text |Cite
|
Sign up to set email alerts
|

Governance in mental healthcare policies during the COVID-19 pandemic in Mexico

Abstract: The COVID-19 pandemic has become the greatest burden of disease worldwide and in Mexico, affecting more vulnerable groups in society, such as people with mental disorders (MD). This research aims to analyze the governance processes in the formulation of healthcare policies for people with MD in the face of the COVID-19 pandemic. An analytical qualitative study, based on semi-structured interviews with key informants in the healthcare system was conducted in 2020. The study followed the theoretical-methodologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Here, numerous authors have confirmed the influence of knowledge transfer in improving health outcomes. Based on these studies, we emphasize the importance of education and knowledge transfer in improving the effectiveness of global health alliances [ 36 , 93 , 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, numerous authors have confirmed the influence of knowledge transfer in improving health outcomes. Based on these studies, we emphasize the importance of education and knowledge transfer in improving the effectiveness of global health alliances [ 36 , 93 , 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mental health costs are the highest single source of global economic burden in the world [ 35 ], and adolescence is the peak time for clinical onset of most mental illnesses [ 21 ]. Yet access to mental health services are low or uneven in many countries including Mexico, where less than 1% of Mexico’s Ministry of Public Health total budget is dedicated to mental health [ 27 ]. Out of pocket expenditures in Mexico have been steadily increasing, reaching 41.3% in 2017, with higher likelihood of catastrophic healthcare expenditures for mental health issues [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet access to mental health services are low or uneven in many countries including Mexico, where less than 1% of Mexico’s Ministry of Public Health total budget is dedicated to mental health [ 27 ]. Out of pocket expenditures in Mexico have been steadily increasing, reaching 41.3% in 2017, with higher likelihood of catastrophic healthcare expenditures for mental health issues [ 27 ]. As a result, issues such as climate change that may drive economic losses and disruptions may exacerbate CMD and also create an additional financial stressor on households.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research is relatively new from the perspective of policy governance. Based on the identification of previous research, governance studies have been widely used as an analytical tool to study policies in various sectors, including the governance analytical framework (Diaz-Castro et al, 2023;Liang et al, 2015;Syahrir et al, 2021).…”
Section: Introductionmentioning
confidence: 99%